Thirty years of interactive learning environments: contributors, collaborations and research topics. (29th July 2022) - Chen, Xieling; Zou, Di; Cheng, Gary; Xie, Haoran
Interactive Learning Environments (ILE) is an important and active international journal in the research field of interactive learning environments since 1990. Focusing on the major contributors, scientific collaborations, research topics and topic evolution, this paper analyses 784 ILE articles using topic modelling and bibliometrics to explore key milestones in ILE's history. Institutions from the USA and Taiwan have contributed the most to the community, as witnessed from their top ranks in both impact and productivity indicators. Scientific collaborations between institutions in the same regions are noteworthy, while cross-regional collaborations need to be enhanced. Diverse applications and technologies such as intelligent tutoring systems, concept maps, digital games, e-books, interactive response systems, digital storytelling and augmented reality are increasingly integrated into interactive learning contexts to facilitate flipped learning, personalised learning and project-based learning. Additionally, learners' emotions, cognitive load and acceptance of technologies are widely studied.